Arsenic Contamination of Drinking Water and Mental Health - Shyamal Chowdhury; Annabelle Krause; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2015)
This paper investigates the effect of drinking arsenic contaminated water on mental health. Drinking water with an unsafe arsenic level for a prolonged period can lead to arsenicosis, which includes symptoms such as black spots on the skin and subsequent illnesses such as various cancers. We collected household survey data from Bangladesh, a country with wide arsenic contamination of groundwater to construct several measures for arsenic contamination that include the actual arsenic level in the respondent's tubewell (TW) and past institutional arsenic test results, as well as collected household members' arsenicosis symptoms and their physical and mental health. We find that suffering from an arsenicosis symptom is strongly negatively related to mental health, even more so than from other illnesses. Furthermore, individuals drinking from an untested TW have lower mental health and having to walk a longer distance to a TW also decreases mental health. Calculations of the costs of arsenic contamination reveal that the average individual would need to be compensated for suffering from an arsenicosis symptom by an amount as high as the average annual household income.
Keywords: Q53; I10; I31; 330; arsenic; water pollution; mental health; subjective well-being; environment; Bangladesh